2002
DOI: 10.1039/b210421k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of scintillant-containing poly(oxyethylene glycol) polymer (POP-Sc) supports

Abstract: Co-polymerisation of a-styryl-poly(ethylene glycol) 300 , a,v-bis(styryl)-penta(ethylene glycol) and 2,5-diphenyl-4-(4'-vinylbenzyl)oxazole in varying molar ratios resulted in the production of chemically functionalised scintillant-containing poly(oxyethylene glycol) polymer (POP-Sc) supports. These materials are compatible with both aqueous and organic solvents, and possess the ability to scintillate efficiently in the presence of ionising radiation, even after prolonged and repeated exposure to organic solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In contrast, PEG-based supports in contact with water exhibit greater swelling and mass-water uptake compared with styrenebased supports. 9,10 Again this observation was found to be in excellent agreement with the greater initial rate and extent of hydrolysis in water of PEG-based support 7 (kA = 0.021 h 21 , 37% @ 28 h) compared with styrene-based support 8 (kA = 0.004 h 21 , 15% @ 28 h).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…In contrast, PEG-based supports in contact with water exhibit greater swelling and mass-water uptake compared with styrenebased supports. 9,10 Again this observation was found to be in excellent agreement with the greater initial rate and extent of hydrolysis in water of PEG-based support 7 (kA = 0.021 h 21 , 37% @ 28 h) compared with styrene-based support 8 (kA = 0.004 h 21 , 15% @ 28 h).…”
supporting
confidence: 66%
“…Previous swelling and mass-solvent uptake studies with non-polar solvents demonstrated that styrenebased polymer supports swell far more and imbibe a greater mass of solvent than PEG-based supports when brought into contact with the same solvent. 9,10 This observation suggests that a solution of KOH/18-C-6/benzene will permeate into styrene-based matrices more rapidly than PEG-based matrices. This supposition fits exactly with the observation that hydrolysis of [ 3 H]acetate ester from styrene-based polymer 8 (kA = 0.693 h 21 , 99% @ 28 h) initially proceeds seven times faster and more fully to completion compared with that observed for PEG-based support 7 (kA = 0.095 h 21 , 85% @ 28 h).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that radioactive sources can induce scintillations in aromatic solvents that contained certain solutes [5]. These early beginnings of 'liquid scintillation (LS) counting' led to rapid advances in counting instrumentation and to the development of scintillation 'cocktails' to where it quickly became a routine method for measuring the concentration of β − emitting radionuclides such as 3 H and 14 C in a variety of samples matrices. These samples are normally mixed with an LS cocktail composed of an organic solvent containing waterinsoluble fluor molecules that emit light upon interacting with the emitted radioactive particles.…”
Section: Introductionmentioning
confidence: 99%
“…The compatibility of POPAM support 8 with a variety of solvents was determined by evaluating the percentage volume increase of 8 upon contact with solvent by utilizing a swelling assay procedure. , The percentage volume increase data obtained from this swelling assay established that 8 swells significantly with both aqueous solvent (water, 900%) and organic solvents (DCM, 1150%; tetrahydrofuran (THF), 900%; DMF, 900%; and toluene, 850%).…”
mentioning
confidence: 99%